A comprehensive approach to managing a neglected, neglected tropical disease; The Myanmar Snakebite Project (MSP). (January 2019) - White, Julian; Mahmood, Mohammad Afzal; Alfred, Sam; Thwin, Khin Thida; Kyaw, Khin Maung; Zaw, Aung; Warrell, David; Cumming, Robert; Moody, John; Eagles, Debbie; Ragas, Keiran; Dunstan, Nathan; et al.
Abstract: Snakebite is predominantly an occupational disease affecting poor rural farmers in tropical regions and was recently added to the World Health Organisation list of Neglected Tropical Diseases (NTD). We document an overview of methodologies developed and deployed in the Myanmar Snakebite Project, a foreign aid project largely funded by the Australian Government, with the core aim to "improve outcomes for snakebite patients". A multidisciplinary team of experts was assembled that worked in a collaborative manner with colleagues in Myanmar, first to identify problems related to managing snakebite and then develop interventions aimed to improve selected problem areas. A broad approach was adopted, covering antivenom production, antivenom distribution and health system management of snakebite. Problems identified in antivenom production included poor snake husbandry resulting in poor survival of captive specimens, lack of geographical diversity; poor horse husbandry, resulting in high mortality, inadequate stock acquisition protocols and data collection, and inappropriate immunisation and bleeding techniques; and inadequate production capacity for freeze dried antivenoms and quality control systems. These problems were addressed in various ways, resulting in some substantial improvements. Antivenom distribution is being reorganised to achieve better availability and utilisation of stock. Health system management of snakebite was assessed across all levels within the area selected for the study, in Mandalay region. A comprehensive community survey indicated that hospital statistics substantially underestimated the snakebite burden, and that access to care by local villagers was delayed by transport and cost issues compounded by lack of antivenom at the most peripheral level of the health service. A health system survey confirmed under-resourcing at the local village level. Prospective case data collection initiated at tertiary hospitals indicated the extent of the snakebite burden on health resources. Interventions initiated or planned include training of health staff, development of a core of senior trainers who can "train the trainers" nationwide in a sustainable way, development and deployment of management guidelines and algorithms for snakebite and a distribution of solar powered fridges to remote health facilities to allow storage of antivenom and prompt treatment of snakebite cases before transfer to major hospitals, thereby reducing the "bite to needle" time. Highlights: Documents an international aid project in Myanmar to improve outcomes for snakebite patients. 3 focus areas; improving antivenom production, availability, and care of snakebite patients. Emphasizes a broad approach and importance of inter-ministerial government collaboration. Emphasizes sustainable improvements through health services strengthening and training. Community involvement, education and use of local community surveys are described and advocated.